2015
DOI: 10.5117/2015.043.002.169
|View full text |Cite
|
Sign up to set email alerts
|

Demografische diversiteit in het Vlaamse perslandschap

Abstract: Demographic diversity in the Flemish press Demographic diversity in the Flemish press This study analyses the diversity of the Flemish news by looking at demographic diversity, i.e. the extent to which gender, age and ethnicity in society are proportionally represented in the news. In a constructed week (April-May 2012) (N = 4,800) 12,743 persons were mentioned, each of them were assigned to age groups, man or woman, ethnic minority or ethnic majority. The results indicate that yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Overall, it can be concluded that women seem to be covered more in typical “soft” news topics (cfr. Reinemann et al, 2012), whereas they have much less chance to appear in hard news topics such as politics and economy (Global Media Monitoring Project, 2020; Sjøvaag & Pedersen, 2019; Vandenberghe et al, 2015). Based on these previous studies, we thus expect that news topic will be a predictor of the presence of women as speaking actors in the news.…”
Section: Predicting Gender Diversity In the Newsmentioning
confidence: 99%
“…Overall, it can be concluded that women seem to be covered more in typical “soft” news topics (cfr. Reinemann et al, 2012), whereas they have much less chance to appear in hard news topics such as politics and economy (Global Media Monitoring Project, 2020; Sjøvaag & Pedersen, 2019; Vandenberghe et al, 2015). Based on these previous studies, we thus expect that news topic will be a predictor of the presence of women as speaking actors in the news.…”
Section: Predicting Gender Diversity In the Newsmentioning
confidence: 99%